Nanostructured films of perylene derivatives: High performance materials for taste sensor applications - Constantino, C. J L [UNESP]; Antunes, P. A. [UNESP]; Venancio, E. C.; Consolin, N.; Fonseca, F. J.; Mattoso, L. H C; Aroca, R. F.; Oliveira, O. N.; Riul, A. [UNESP] (My University, 2004)
Four perylene derivatives (PTCD) have been used as transducing materials in taste sensors fabricated with nanostructured Langmuir-Blodgett (LB) films deposited onto interdigitated gold electrodes. The Langmuir monolayers of PTCDs display considerable collapse pressures, with areas per molecule indicative of an edge-on or head-on arrangement for the molecules at the air/water interface. The sensing units for the electronic tongue were produced from 5-layer LB films of the four PTCDs, whose electrical response was characterized with impedance spectroscopy. The distinct responses of the PTCDs, attributed to differences in their molecular structures, allowed one to obtain a finger printing system that was able to distinguish tastes (salty, sweet, bitter and sour) at 1 μM concentrations, which, in some cases, are three orders of magnitude below the human threshold. Using Principal Component Analysis (PCA) data analysis, the electronic tongue also detected trace amounts of a pesticide and could distinguish among samples of ultrapure, distilled and tap water, and two brands of mineral water. © 2004 by American Scientific Publishers. All rights reserved.
Keywords: Electronic tongue; Langmuir-Blodgett; Perylene; Sensors; Thin films; Dyes; Electrodes; Interfaces (materials); Isotherms; Langmuir Blodgett films; Molecular structure; Nanostructured materials; Pesticides; Principal component analysis; Spectroscopy; Impedance spectroscopy; Nanostructured films; Organic dyes; Taste sensor